Workshop on Writing a Review of Relevant Literature in a Research Report for English Teachers in Bogor - Anna Marietta da Silva (Institute for Research and Community Services, 2019)
The workshop on writing a review of relevant literature in a research paper is part of a series of workshop given to English teachers of Bogor Regency. The workshop series is part of the cooperation between Atma Jaya Catholic University of Indonesia and Pakuan University in terms of research and community service. The theme was chosen because of the needs of the teachers to write and publish their classroom action research report for their professional development. Therefore the goal of the workshop is to assist and guide the teachers in their report writing, particularly the literature review. The workshop consisted of explanation about a literature review of a research article, steps to write a review and analysis of samples of reviews. The participants mostly appreciated the content of the workshop and hoped that the following workshop theme will either extend the given materials or cover skills of writing other sections of a research article. They also gave some suggestions related to the technique of delivery and duration of the workshop.